(untitled) - The World Bank in Vietnam (WB) (Hà Nội, 2004)
The objective of the Forest Sector Development Project (FSDP) for Vietnam is to achieve sustainable management of plantation forests and the conservation of biodiversity in special use forests. The project consists of four components: institutional development; smallholder plantation forest; special use forest; and project management and monitoring and evaluation (M&E). Of these, the smallholder plantation forest and the special use forest components are the two main investment components. The purpose of the project restructuring is to: reallocate proceeds of the International Development Association (IDA) credit and the Global Environment Facility (GEF) grant to eliminate category overdraws and account for adjusted funding needs during the extension period as per agreed work plans; and adjust the project description of schedule two of the Development Credit Agreement (DCA) and all associated trust fund agreements to be more specific with regard to eligible project activities also covering: the improvement and repair of existing plantation access tracks and forest fire break lines, upgrading of nursery facilities, and international study tours under part B of the project
Keywords: Forestry public administration,Quản lý lâm nghiệp; Vietnam,Việt Nam